KONFLIK BATIN TOKOH UTAMA DALAM NOVEL KAMUKAH ITU AI KARYA YULISMAR - Suci Susanti; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research titled inner conflict in novel you are Ai by Yulismar. The purpose of this research is to describe the inner conflicts of the main character in the novel of you are Ai by Yulismar. Describes the cause of the inner conflicts of the main character in the novel you are Ai by Yulismar. Describe the solution of the inner conflict in novel you are Ai by Yulismar. The result of inner conflict research in the novel has been observed that the inner conflicts amount to 30 data, the cause of the inner conflict amounted to 30 and the completion of the inner conflict amounted to 30 data. The total data is 90 data. The inner conflicts felt by the main character are more tantalistic to avoidance of dodge. The cause of the inner conflicts experienced by the main character is more caused by other figures or external. While the settlement experienced by the main character more on the internal settlement or only the main character who know it.Keywords: Conflict, Inner, Main Figure, Novel